Concrete Mixtures with High Microfines - Quiroga, Pedro Nel; Ahn, Namshik; fowler, david (American Concrete Institute, 2006)
Two projects were performed to evaluate the effect of the amount and type of microfines (material passing the No. 200 sieve), as well as the effect of shape, texture, and grading of aggregates on concrete behavior. In the first project, several manufactured fine aggregates (MFA) and one natural sand were used for mortar and concrete mixtures, without chemical admixtures. Generally, concrete with MFA was stiffer and less workable than concrete with natural sand, but in most cases MFA resulted in higher compressive and flexural strengths, higher resistance to chloride penetration, and higher abrasion resistance. In the second project, five aggregates with varied shape and texture were used to make concrete with microfines, chemical admixtures, and supplementary cementing materials. Significant variations due to the combined effect of shape and texture of aggregate, grading, and the type and amount of microfines were found. It was also found that chemical admixtures and cementing materials can be used to enhance workability of concrete with high microfines.

Se realizaron dos proyectos para evaluar el efecto de la cantidad y el tipo de microfinos (material que pasa el tamiz n.º 200), así como el efecto de la forma, la textura y la clasificación de los áridos en el comportamiento del hormigón. En el primer proyecto, se utilizaron varios áridos finos manufacturados (MFA) y una arena natural para mezclas de mortero y hormigón, sin aditivos químicos. En general, el hormigón con AMF era más rígido y menos manejable que el hormigón con arena natural, pero en la mayoría de los casos el AMF dio lugar a mayores resistencias a la compresión y a la flexión, mayor resistencia a la penetración de cloruros y mayor resistencia a la abrasión. En el segundo proyecto, se utilizaron cinco áridos de forma y textura variadas para fabricar hormigón con microfinas, aditivos químicos y materiales cementantes suplementarios. Se observaron variaciones significativas debidas al efecto combinado de la forma y textura del árido, la granulometría y el tipo y cantidad de microfinas. También se descubrió que los aditivos químicos y los materiales cementantes pueden utilizarse para mejorar la trabajabilidad del hormigón con alto contenido en microfinas.
Keywords: Admixtures; Aggregates; Grading; Sand